With the "universal definition," measurement of creatine kinase-myocardial band rather than troponin allows more accurate diagnosis of periprocedural necrosis and infarction after coronary intervention - Lim, Chris C S; van Gaal, William J; Testa, Luca; Cuculi, Florim; Arnold, Jayanth R; Karamitsos, Theodoros; Francis, Jane M; Petersen, Steffen E; Digby, Janet E; Westaby, Stephen; Antoniades, Charalambos; Kharbanda, Rajesh K; et al. (Journal of the American College of Cardiology, 2011)
We aimed to assess the differential implications of creatine kinase-myocardial band (CK-MB) and troponin measurement with the universal definition of periprocedural injury after percutaneous coronary intervention. Differentiation between definitions of periprocedural necrosis and periprocedural infarction has practical, sociological, and research implications. Troponin is the recommended biomarker, but there has been debate about the recommended diagnostic thresholds. Thirty-two patients undergoing multivessel percutaneous coronary intervention and late gadolinium enhancement (LGE) cardiac magnetic resonance (CMR) imaging in a prospective study had cardiac troponin I, CK-MB, and inflammatory markers (C-reactive protein, serum amyloid A, myeloperoxidase, tumor necrosis factor alpha) measured at baseline, 1 h, 6 h, 12 h, and 24 h after the procedure. Three "periprocedural injury" groups were defined with the universal definition: G1: no injury (biomarker <99th percentile); G2: periprocedural necrosis (1 to 3 × 99th percentile); G3: myocardial infarction (MI) type 4a (>3 × 99th percentile). Differences in inflammatory profiles were analyzed. With CK-MB there were 17, 10, and 5 patients in groups 1, 2, and 3, respectively. Patients with CK-MB-defined MI type 4a closely approximated patients with new CMR-LGE injury. Groups defined with CK-MB showed progressively increasing percentage change in C-reactive protein and serum amyloid A, reflecting increasing inflammatory response (p < 0.05). Using cardiac troponin I resulted in 26 patients defined as MI type 4a, but only a small minority had evidence of abnormality on CMR-LGE, and only 3 patients were defined as necrosis. No differences in inflammatory response were evident when groups were defined with troponin. Measuring CK-MB is more clinically relevant for diagnosing MI type 4a, when applying the universal definition. Current troponin thresholds are oversensitive with the arbitrary limit of 3 × 99th percentile failing to discriminate between periprocedural necrosis and MI type 4a. (Myocardial Injury following Coronary Artery bypass Surgery versus Angioplasty: a randomised controlled trial using biochemical markers and cardiovascular magnetic resonance imaging; ISRCTN25699844).